Formation Mechanism and Evolution of Plastic Damage in Billet during Reduction Pretreatment - Yang Liu; Jianhua Liu; Yang He (Metals, 2023)
The formation mechanism and evolution of plastic damage in billet during reduction pretreatment were investigated using laboratory experiments and simulations. The microstructure and damage distribution were observed using reduction pretreatment experiments. Isothermal tension tests were designed to study the mechanism of damage under different deformation temperatures and strain rates. A plastic damage model based on tension tests was established to further analyze damage evolution during reduction pretreatment. Experimental results showed that the distribution of the damage was characterized by microvoids near the surface and microcracks along the grain boundary at the center. With the increase in strain rate, plastic damage above 1050 °C was transformed from grain boundary damage caused by grain boundary slip to inclusion damage caused by dislocation movement. The simulation results showed that the established plastic damage model was reliable and could be used to describe the plastic damage evolution during reduction pretreatment.